PENGARUH LITERASI KEUANGAN SYARIAH, MANFAAT, DAN RISIKO TERHADAP MINAT MENGGUNAKAN SHOPEE PAYLATER PADA MAHASISWA SURABAYA: THE INFLUENCE OF SHARIA FINANCIAL LITERACY, BENEFITS, AND RISKS ON INTEREST IN USING SHOPEE PAYLATER AMONG SURABAYA STUDENTS - Afif, Zamitah Tahiyyah; Indrarini, Rachma (Universitas Negeri Surabaya, 2024)
The payment system in Indonesia is evolving with the presence of financial technology, one of which is shopee paylater. Currently, shopee paylater is widely used by the Indonesian community. This can be seen from a survey indicating that Shopee Paylater outperforms other pay-later services. This research aims to determine whether there is an influence of islamic financial literacy, benefits, and risks on the interest in using shopee paylater. The research method used is a quantitative approach with an associative research method. The data used in this study are from a survey of 150 respondents obtained through non-probability sampling using purposive sampling technique. The data were analyzed using SmartPLS 4.0. The results of this study indicate that, Islamic financial literacy has a positive influence on the interest in using shopee paylater among students in Surabaya. Benefits have a positive influence on the interest in using shopee paylater among students in Surabaya. And Risks do not influence the interest in using shopee paylater among students in Surabaya.